Estimation of Air Conditioning Load for a Lecture Auditorium - genuinely, Ebigenibo; Saturday, E. G. (European Journal of Applied Sciences, 2022)
The estimation of air conditioning load for a lecture auditorium in the Department of Mechanical Engineering, University of Port Harcourt was carried out in this work. The auditorium is at latitude 4.9069°N and longitude 6.9170°E. The grand total heat load of the auditorium was estimated with the use of MATLAB software. The grand total heat load was estimated to pave the way for the installation of appropriate air conditioning units. Parametric analysis was also carried out to determine the effect of different parameters on the grand total heat load. The results showed that an increase in the outdoor temperature and number of glass windows in the building will lead to an increase in the grand total heat load posed on the building if other variable physical parameters are kept constant, while an increase in the indoor temperature of the building will lead to a decrease in the grand total heat load of the building when other variable physical parameters are kept constant. The methodology used in the air conditioning load estimation for this case study can be easily applied to other buildings. The work will be useful to air conditioning engineers, individuals and groups who intend to install air conditioning systems in homes and auditoriums